Potential of Analog Meatballs Made from Tempeh and Seaweed as An Alternative Food for Hypertension Patients - Firdaus Syafii; Hasmar Fajriana; Ahmad Yani; Venny Patricia (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2023)
This study aims to determine the effect of the formulation of the use of tempeh and seaweed on the organoleptic properties of meatball analogues. The formulation used in this study was based on the ratio of differences in the use of tempeh and seaweed. The design used in this study was a complete randomized design (RAL). The factors used in this study were 5 formulations with a ratio of tempeh and seaweed, namely F1 (100: 0), F2 (90: 10), F3 (80: 20), F4 (75: 25), and F5 (70: 30). The parameters measured in this design are hedonic tests (favorability levels) which include taste, aroma, color, texture, and over all attributes. Based on the results of hedonic test analysis on 5 formulas using the ANOVA test, it shows that the difference in the ratio of tempeh and seaweed in the formulation of making analog meatballs has a significant effect on the sensory attributes of taste, aroma, texture, and overall (p<0.05) and has no real effect on color attributes (p>0.05). The F3 formulation with tempeh and seaweed ratio (80:20) in the manufacture of analog meatballs gives different values and is the formula that has the most preferred acceptance rate based on the attributes of taste (4.24), aroma (4.23), and texture (3.97), and overall (4.36). Meatball analogue with the most preferred formula of the results of this study can be used as an alternative food for consumption by people with hypertension